Evaluation and Social Internship Program of IAIN Sultan Thaha Saifuddin Jambi Students: Using Context, Input, Process and Product Model (CIPP Model) - Hurmaini, Muhammad (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
The purpose of the research is to know the context, input, process and product evaluation on the Social Internship Program (Kukerta) of IAIN Sulthan Thaha Saifuddin Jambi Students by using Participatory Action Research (PAR) system. The research is conducted in four locations ofÂ Â IAIN Sultan Thaha Saifuddin Jambi studentsâ Kukerta in first period of 2013; Lubuk Terap, Sengeti Kecamatan Sekernan, unas, and Simpang Tiga Sipin by using questionnaire. All students of Kukerta in these 4 locations, consists of 51 people become the sample of this study. The finding of the study showed that first, context evaluation ofÂ PARÂ system Kukerta programs is actually having many deficiencies and weakness in both determining the needs as well as the purpose of Kukerta program. Therefore, it needs some improvements or revision. Second, input evaluation ofÂ Â PAR system Kukerta shows some weakness from the students and the internship supervisors/ advisors. Both students and internship supervisors have to be firstly provided by training onÂ Â PAR system Kukerta. Third, process evaluation on the program is also lack of the relevant activities towards studentsâ needs and program realization. Fourth, product evaluation reveals that there is no significant result of the program, physically or non-physically. It can be recommended that the program can be continued with some improvements and revision on its implementation.Â Copyright Â© 2015 by Al-Talim All right reserved